Revising Tell Abu Hawam - Balensi, Jacqueline (Bulletin of ASOR, 1985)
New interpretations of data from Tell Abu-Hawam-the original harbor of Haifa-are based largely on the original reports of R. W. Hamilton. Concentrating on Hamilton's 1932-33 campaigns, much hitherto unpublished material is being analyzed. Because they had been labelled in the field, these items can prove valuable not only for typological studies but for a stratigraphically-based revision of the chronology as well. Traces of occupation as early as M B II have been attested by a few finds, although most evidence is from somewhat later, and Greek imports as late as the 6th and 5th centuries b. c. have been found.